Therapy of asymptomatic bacteriuria in pregnant women as prevention of gestational pyelonephritis (LCC «Medicine-Inform», 2019)
Therapy of asymptomatic bacteriuria in pregnant women as prevention of gestational pyelonephritis I.Yu. Ilina Pirogov Russian National Research Medical University, Moscow, Russian Federation Urinary tract infections are common in daily clinical practice. In pregnancy, the most common pathological condition is asymptomatic bacteriuria. Late antibacterial treatment regardless of microbial susceptibility may result in ascending infections which provoke gestational pyelonephritis and other complications. In addition, increasing antimicrobial resistance presents difficulties for urinary tract sanitation during pregnancy. Aim: to evaluate the efficacy of fosfomycin to treat asymptomatic bacteriuria and to prevent gestational pyelonephritis in the second trimester. Patients and Methods: 78 pregnant women in the second trimester with verified asymptomatic bacteriuria were examined. Group 1 received fosfomycin trometamol, group 2 received amoxicillin plus clavulanic acid, group 3 refused antibacterial treatment (despite potential consequences) and received phytotherapy. Results: comparative analysis demonstrates positive correlation (moderate-to-high) between chronic urinary tract disorders, the number of spontaneous miscarriage, anamnestic preterm birth, and threatened abortion. Published data confirm this observation. It was demonstrated that after 1 and 3 months of the treatment asymptomatic bacteriuria was similar in group 1 and 2 (6.7%) while in group 3 the occurence of asymptomatic bacteriuria was 94.4%. Later, gestational pyelonephritis has developed in group 3 only (16.7%). Conclusion: fosfomycin trometamol is effective for asymptomatic bacteriuria and prevention of acute urinary tract infections in pregnant women. Key words: asymptomatic bacteriuria, urinary tract infections, pregnancy, antibacterial, gestational pyelonephritis, fosfomycin trometamol. For citation: Ilina I.Yu. Therapy of asymptomatic bacteriuria in pregnant women as prevention of gestational pyelonephritis. Russian Journal of Woman and Child Health. 2019;2(1):5-9.